2014
DOI: 10.2142/biophysics.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characteristics of feeding-related neurons after taste avoidance Pavlovian conditioning in Lymnaea stagnalis

Abstract: Taste avoidance conditioning (TAC) was carried out on the pond snail, Lymnaea stagnalis. The conditional stimulus (CS) was sucrose which elicits feeding behavior; while the unconditional stimulus (US) was a tactile stimulus to the head which causes feeding to be suppressed. The neuronal circuit that drives feeding behavior in Lymnaea is well worked out. We therefore compared the physiological characteristics on 3 classes of neurons involved with feeding behavior especially in response to the CS in conditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The ability of snails to undergo configurational learning is an ulterior confirmation of its potentiality in neuroscience and behavioural research (Swinton et al, 2019). Depending on the training procedure used, either intermediate term-memory (ITM; persisting up to 3 h) or LTM (persisting for at least 24 h) occurred in L. stagnalis (Kojima et al, 1996;Benjamin et al, 2000;Sangha et al, 2003c;Ito et al, 2013;Otsuka et al, 2013;Takahashi et al, 2013;Lukowiak et al, 2014;Sunada et al, 2014). Because the inhibition of transcription or translation blocked the formation of LTM in a variety of model systems, but did not affect short-term memory (STM), it has been concluded that this phase, lasting only minutes, does not require neither de novo protein nor RNA synthesis (De Zazzo and Tully, 1995).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The ability of snails to undergo configurational learning is an ulterior confirmation of its potentiality in neuroscience and behavioural research (Swinton et al, 2019). Depending on the training procedure used, either intermediate term-memory (ITM; persisting up to 3 h) or LTM (persisting for at least 24 h) occurred in L. stagnalis (Kojima et al, 1996;Benjamin et al, 2000;Sangha et al, 2003c;Ito et al, 2013;Otsuka et al, 2013;Takahashi et al, 2013;Lukowiak et al, 2014;Sunada et al, 2014). Because the inhibition of transcription or translation blocked the formation of LTM in a variety of model systems, but did not affect short-term memory (STM), it has been concluded that this phase, lasting only minutes, does not require neither de novo protein nor RNA synthesis (De Zazzo and Tully, 1995).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Snails are able to consolidate the associative learning into long-term memory (LTM) (Benjamin et al, 2000;Otsuka et al, 2013;Takahashi et al, 2013;Lukowiak et al, 2014;Sunada et al, 2014). Here, we look at the ability of Lymnaea to learn and remember for many days not to respond to a food substance that normally elicits a feeding response.…”
Section: Introductionmentioning
confidence: 99%
“…Because the B3 cell receives an inhibitory input from the N1M cell (Staras et al 1998;Fig. 2b), the B3 cell was expected to be suppressed in taste aversion-trained snails, and that is what they found (Sunada et al 2014).…”
Section: Conditioned Taste Aversion In Snailsmentioning
confidence: 79%
“…From their experiments, they have constructed a model that differs from the Kojima model described above (Sunada et al 2014). In their model, there is no change in the synaptic input from the CGC to the N1M cell after CTA-LTM.…”
Section: Conditioned Taste Aversion In Snailsmentioning
confidence: 99%